Financial Strategy: An Analysis of Fee-Based Income, Interest Income, and Interest Expense on Bank Profitability - Anita Putri (Yayasan Multidimensi Kreatif, 2024)
This study aims to determine how interest-based income, interest expense, and interest income impact the net profit of commercial banks listed on the Indonesia Stock Exchange. This data was obtained from www.idx.co.id from 2018-2023, and this study will start in 2024. This study involved 42 companies as population and 25 companies as samples. Eviews 9 application and panel regression method were used to process quantitative data in this study. The results showed that in commercial banks, interest income and interest expense partially had a significant effect on net profit, but interest-based interest income did not significantly affect net profit. Interest income based on interest has a positive impact, while interest expense has a negative impact. Together, fee-based income, interest expense, and interest income have a positive impact on the net profit of commercial banks from 2018 to 2023. Net profit is influenced the most by interest income. Hypotheses H2, H3, and H4 are proven to be true and acceptable as the research results are in line with the hypotheses. In contrast, hypothesis H1 is rejected and cannot be accepted because the research results are not in line with the hypothesis. The level of closeness of interest-based income, interest income, and interest expense variables to net income is very close or very strong, with an R value of 0.976.